The gut-liver axis in fatty liver disease: role played by natural products - Ming, Zhu; Ruishi, Xie; Linyi, Xu; Yonggang, Yang; Haoming, Luo; Xintian, Lan (Frontiers in Pharmacology, 2024)
Fatty liver disease, a condition characterized by fatty degeneration of the liver, mainly classified as non-alcoholic fatty liver disease (NAFLD) and alcoholic liver disease (ALD), has become a leading cause of cirrhosis, liver cancer and death. The gut-liver axis is the bidirectional relationship between the gut and its microbiota and its liver. The liver can communicate with the gut through the bile ducts, while the portal vein transports the products of the gut flora to the liver. The intestinal flora and its metabolites directly and indirectly regulate hepatic gene expression, leading to an imbalance in the gut-liver axis and thus contributing to the development of liver disease. Utilizing natural products for the prevention and treatment of various metabolic diseases is a prevalent practice, and it is anticipated to represent the forthcoming trend in the development of drugs for combating NAFLD/ALD. This paper discusses the mechanism of the enterohepatic axis in fatty liver, summarizes the important role of plant metabolites in natural products in fatty liver treatment by regulating the enterohepatic axis, and provides a theoretical basis for the subsequent development of new drugs and clinical research.